ANALISIS KEMAMPUAN SPATIAL REASONING, VISUALISASI, DAN REPRESENTASI MATEMATIS PADA PENYELESAIAN SOAL GEOMETRI RUANG - Adhi Surya Nugraha (Program Studi Pendidikan Matematika FMIPA Universitas PGRI Banyuwangi, 2026)
This study aims to describe the spatial reasoning, visualization, and mathematical representation abilities of Mathematics Education students in solving two spatial geometry problems. The study used a mix method with a descriptive approach. The subjects were 19 students from the class of 2025. Data collection was carried out by a test using two questions. The first question relates to determining the shortest path on the surface of a cube through unfolding, while the second question relates to determining the distance from a point to a plane on the cube. Subjects’ answers were categorized into four quality levels: category A (correct and complete answer), B (initial model is correct but incomplete), C (major strategy or representation error), and D (strategy cannot be operationally formalized). The data show that 9 subjects fell into category B, 9 subjects fell into category C, and 1 subject fell into category D. In the first question, the average subject had a moderate level of spatial reasoning and representation, with visualizations already quite apparent. Subjects tended to be able to construct mathematical visualizations and representations, although some had not yet provided a complete minimum justification. In the second question, the average subject had a low level of spatial reasoning and representation, with visualizations beginning to appear but lacking operational capabilities. Subjects experienced more fundamental difficulties, particularly in constructing planes, determining relevant distances, and formalizing relationships between lines. These results point to the need to emphasize representation translation, mathematical modeling, and argument validation in geometry learning.